New rules or no rules? a critical corpus analysis of gender in South African English televised-sport commentary - Foster, Gordon (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This research project makes use of multiple linguistic and sociological theories. Using Critical Discourse Analysis (as developed by Fairclough 2001, 2013, Wodak 1995, 1997, and van Dijk 2001), and corpus linguistics (following Baker 2012, Baker et al., 2008 and Xiao & McEnery, 2005 - see Website Reference 4), it attempts to critically discuss the language evident in a corpus constructed from transcribed sport broadcasts televised in South Africa, interrogated with the use of AntConc software, maintaining a particular focus on gender representation. It does this with the help of CMT (Contemporary Metaphor Theory) as developed by Lakoff and Johnson (1980) and Lakoff (1993), which allows for the deconstruction and categorisation of metaphorical mappings in the data. With the help of CMT I describe the cognitive mapping of competition through war terminology and uncover a diligent committal to discourses which support hegemonic masculinity, as well as an underlying ideology that purports that rules are breakable and rule infringement will not be significantly penalised (particularly for men). Special attention is paid to collocating language and the ability of these terms to infuse a subject with an evaluative aura. This involves, in particular: using wordlists to identify pertinent content words in the corpus, addressing collocates to reveal semantic prosodies in the text, and analysing concordance data to see how particular discursive strategies were used in context. Particular interest is paid to the depictions of masculinity seen in sport as a potential reflection of the views held in competitive sport playing societies at large, and to this end it focuses on language and imagery which is used in the discursive construction of the terms: men, women, champion, and physicality. The ideology of male hegemony is found to be dominant in the corpus data, seen in, among other things: the positioning of women, the inclusion of traditional discourses relating to the performance of masculinity and the construction of the 'new man'. White, heterosexual men are shown to be represented as exemplars of hegemonic masculinity, subordinating both black and homosexual men. Laughter is also seen as affirmation of the naturalised cheekiness of men and boys and their tendency to break rules in order to succeed, and betting is identified as a potentially destructive influence in sport.
Keywords: Critical discourse analysis; Sportscasters -- Language; Masculinity in sports; Masculinity in mass media; Mass media and sports; Competition (Psychology)